Potential Implications for Designing Drugs Against the Brown Spider Venom Phospholipase‐D. Issue 4 (26th October 2016) - Chaves‐Moreira, Daniele; de Moraes, Fábio Rogério; Caruso, Ícaro Putinhon; Chaim, Olga Meiri; Senff‐Ribeiro, Andrea; Ullah, Anwar; da Silva, Luciane Sussuchi; Chahine, Jorge; Arni, Raghuvir K.; Veiga, Silvio Sanches
ABSTRACT: Loxoscelism refers to the clinical symptoms that develop after brown spider bites. Brown spider venoms contain several phospholipase‐D isoforms, which are the main toxins responsible for both the cutaneous and systemic effects of loxoscelism. Understanding of the phospholipase‐D catalytic mechanism is crucial for the development of specific treatment that could reverse the toxic effects caused by the spider bite. Based on enzymatic, biological, structural, and thermodynamic tests, we show some features suitable for designing drugs against loxoscelism. Firstly, through molecular docking and molecular dynamics predictions, we found three different molecules (Suramin, Vu0155056, and Vu0359595) that were able to bind the enzyme's catalytic site and interact with catalytically important residues (His12 or His47) and with the Mg 2+ co‐factor. The binding promoted a decrease in the recombinant brown spider venom phospholipase‐D (LiRecDT1) enzymatic activity. Furthermore, the presence of the inhibitors reduced the hemolytic, dermonecrotic, and inflammatory activities of the venom toxin in biological assays. Altogether, these results indicate the mode of action of three different LiRecDT1 inhibitors, which were able to prevent the venom toxic effects. This strengthen the idea of the importance of designing a specific drug to treat the serious clinical symptoms caused by the brown spider bite, a public health problem in several parts of the world, and until now without specific treatment. J. Cell. Biochem. 118: 726–738, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The Brown spider phospholipase‐D inhibition abolishes the biological toxic effects. Suramin was an efficiently inhibitor of the Brown spider phospholipase‐D toxin. PLD inhibitors reduced drastically the deleterious effects of Brown spider bite.